Optimalisasi Penerimaan Negara Melalui Zakat Dan Pajak Perspektif Maqâsid Al-Syarî’ah - M. Reza Saputa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In this era of globalization, it is crucial to optimize state revenue through zakat and taxes based on the principles of maqâsid al-syarî’ah. This article presents challenges and opportunities in optimizing both instruments in Indonesia. Through an analysis of state income and zakat potential, a literature review method is employed to formulate an optimization model. The model encompasses increasing public awareness, institutional strengthening, developing supportive regulations, enhancing synergy, and building public trust. The implementation of this model requires commitment from all parties and must be based on the principles of maqâsid al-syarî’ah. Thus, it is hoped that state revenue through zakat and taxes can be optimized to achieve the fair and prosperous goals of national development.